Identification of a novel IGSF1 variant in two Malaysian malesiblings with central hypothyroidism and macroorchidism - Lee, Yee Lin; Ting, Tzer Hwu; Lim, Chong Teik; Thilakavathy, Karuppiah; Musa, Nurul Huda; Ling, King Hwa (Galenos Yayinevi, 2024)
Introduction IGSF1 mutation is the commonest cause of mild to moderate isolated central congenital hypothyroidism and has an X-linked recessive inheritance, primarily affecting males. Other notable clinical features are macroorchidism with delayed pubertal testosterone rise, large birth weight, increased body mass index, low prolactin, transient growth hormone deficiency and low prolactin. Case Presentation Two male siblings with central hypothyroidism were found to have a novel IGSF1 c.3467T>A variant that was likely pathogenic based on the family segregation study. The proband, aged 3 years presented at 18 days old with prolonged jaundice while his 16-year-old brother was only detected to have central hypothyroidism after the proband’s genetic analysis result was known. Both siblings were obese, had large birth weights, macroorchidism and low prolactin. The proband’s brother had intellectual disability while the proband had normal development. Conclusion This case study highlights the importance of evaluation for the IGSF1 variant in patients with unexplained central hypothyroidism, especially when accompanied by X-linked inheritance and macroorchidism. Family segregation analysis allows detection of other affected family members or carriers who may also benefit from thyroxine treatment.